2019
DOI: 10.1111/glob.12255
|View full text |Cite
|
Sign up to set email alerts
|

Displaying grandparenting within Romanian transnational families

Abstract: In this article, I use the analytical framework of ‘displaying family relationships’ to explore the transnational grandparenting practices of Romanian families. I discuss the theoretical aspects of the concept of displaying with regard to its scope, specificity and manifestation. I emphasize the uniqueness of each instance of displaying, while also revealing the various patterns through which family‐related motivations trigger individual behaviour. Highlighting the intersections between such internal motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The decision to move described above resonate with research observed of PRC grandparenting migrants in Australia, Canada, and the United States and United Kingdom (Da, 2003; Lie, 2010; Xie & Xia, 2011; Zhou, 2012), as well as of grandparenting migration more generally (e.g., Ducu, 2019; Horn, 2019; Nedelcu, 2017; Nedelcu & Wyss, 2019; Plaza, 2000; Treas, 2008; Zickgraf, 2016). Other than to relieve their children's financial burden by helping with childcare duties, supporting the moral and cultural cultivation of the next generation and consolidating familyhood were key reasons for the grandparents to embark upon migration later in the lifecourse.…”
Section: From Care Circulation To Care Technologies As Subjectificationsupporting
confidence: 56%
“…The decision to move described above resonate with research observed of PRC grandparenting migrants in Australia, Canada, and the United States and United Kingdom (Da, 2003; Lie, 2010; Xie & Xia, 2011; Zhou, 2012), as well as of grandparenting migration more generally (e.g., Ducu, 2019; Horn, 2019; Nedelcu, 2017; Nedelcu & Wyss, 2019; Plaza, 2000; Treas, 2008; Zickgraf, 2016). Other than to relieve their children's financial burden by helping with childcare duties, supporting the moral and cultural cultivation of the next generation and consolidating familyhood were key reasons for the grandparents to embark upon migration later in the lifecourse.…”
Section: From Care Circulation To Care Technologies As Subjectificationsupporting
confidence: 56%
“…Through their fulfilment of caregiving obligations, stay-behind families can function, while highly gender dichotomized familial patterns continue to thrive. Contrary to those who argue women's status can be raised when they have earning power, the value of reproductive work is largely overlooked and remains in the hands of women family members, as demonstrated in other countries (Ducu 2020;Yarris 2017). Some stay-behind husbands participate in caregiving at home, but this is because they redefined their masculine identity (Fresnoza-Flot 2014; Hoang and Yeoh 2011).…”
Section: 5mentioning
confidence: 95%
“…The caregiver in Filipino migrant women's households is usually a female member of her immediate or extended kin: notably a migrant's mother, sister, adolescent daughter, aunt, cousin, or mother-in-law (Ducu 2020;Fernández in this volume;Pantea 2012;Save the Children 2006). She assumes the caregiving obligations and domestic chores of the absent mother.…”
Section: Maternal Migration and Shared Motheringmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about them remain rare at this moment (e.g. DANKYI et al, 2017;DUCU, 2020;HOANG, YEOH, 2011;LAHAIE et al, 2009;PANTEA, 2012;PINGOL, 2001;POEZE et al, 2017;YARRIS, 2011YARRIS, , 2012. These works show that caregiving obligations coupled with migrant parents' expectations engender caregivers' stressful situations, which subsequently affects their physical and emotional wellbeing (see also DREBY, 2010).…”
Section: Separation and Reunification In Transnational Families: Carementioning
confidence: 99%